IMPLEMENTASI RANGE OF MOTION (ROM) EXERCISE DINI PADA PASIEN POST ORIF FRAKTUR CRURIS TERHADAP KEMAMPUAN KEKUATAN OTOT DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN - Aptria, Lenny; Olivia, Nina; Pratama, Muchti Yuda (SINERGI : Jurnal Riset Ilmiah, 2026)
Open Reduction Internal Fixation (ORIF) procedures in patients with fractures often result in pain, which leads to limited mobility and decreased muscle strength. These issues can prolong the bone healing process. Early implementation of Range of Motion (ROM) exercises can improve muscle strength, maintain joint flexibility, enhance blood circulation, and accelerate wound healing. This study aims to describe the implementation of early ROM exercises in post-ORIF patients with cruris fractures and their effect on muscle strength. The research method used was a case study design with a nursing care approach, starting from assessment, diagnosis, intervention, implementation, and evaluation, involving two post-ORIF cruris fracture patients. The instrument used was a Manual Muscle Testing (MMT) observation sheet, with data collected through interviews, observation, physical examination, and nursing documentation. The study was conducted in February 2025 over three days, and data were analyzed narratively. The results showed improvements in muscle strength, reduction of pain, and increased joint flexibility through ROM exercises. The study concludes that early ROM exercises demonstrate an increase in muscle strength and a reduction in pain level.